2019
DOI: 10.1038/s41598-019-55226-3
|View full text |Cite
|
Sign up to set email alerts
|

The Alpha Crucis Carbonate Ridge (ACCR): Discovery of a giant ring-shaped carbonate complex on the SW Atlantic margin

Abstract: Recently acquired bathymetric and high-resolution seismic data from the upper slope of Santos Basin, southern Brazilian margin, reveal a major geomorphological feature in the SW Atlantic that is interpreted as a carbonate ridge - the Alpha Crucis Carbonate Ridge (ACCR). The ACCR is the first megastructure of this type described on the SW Atlantic margin. The ~17 × 11-km-wide ring-shaped ACCR features tens of >100-m-high steep-sided carbonate mounds protruding from the surrounding seabed and flanked by elongate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 64 publications
(101 reference statements)
1
37
0
Order By: Relevance
“…Campos et al (2008) and Nagai et al (2014a) used clay mineralogy to indicate sediments from the Río de la Plata to the north. Also, the maps presented by Govin et al The samples from the Santos Basin present lower radiogenic Nd and higher radiogenic Pb values, thus indicating a pre-Cambrian source, as Mantovanelli et al (2018) stated. Nevertheless, the values obtained for Pb isotopes differ significantly from those reported in the literature for the pre-Cambrian metasediments and granites of the southeastern Brazilian coast (Ragatky et al, 2000;Moraes et al, 2004;Mendes et al, 2011).…”
Section: Sediment Sourcesmentioning
confidence: 64%
See 1 more Smart Citation
“…Campos et al (2008) and Nagai et al (2014a) used clay mineralogy to indicate sediments from the Río de la Plata to the north. Also, the maps presented by Govin et al The samples from the Santos Basin present lower radiogenic Nd and higher radiogenic Pb values, thus indicating a pre-Cambrian source, as Mantovanelli et al (2018) stated. Nevertheless, the values obtained for Pb isotopes differ significantly from those reported in the literature for the pre-Cambrian metasediments and granites of the southeastern Brazilian coast (Ragatky et al, 2000;Moraes et al, 2004;Mendes et al, 2011).…”
Section: Sediment Sourcesmentioning
confidence: 64%
“…The contouritic features and submarine canyons actively interact along the margin so that mixed contouritic-gravitational erosive and depositional features are common. Mega-slides (Reis et al, 2016;Franco-Fraguas et al, 2017) and carbonate mounds (Carranza et al, 2012;Maly et al, 2019;Steinmann et al, 2020) are also present along the margin.…”
Section: Morphologymentioning
confidence: 99%
“…This pattern contrasts with other areas, which show more developed contouritic deposits, such as channel-related drifts (Sivkov et al, 2002) or mud-dominated sediment drifts (either sheeted or elongated), particularly documented in the Mediterranean Sea (Verdicchio and Trincardi, 2008;Vandorpe et al, 2011;Pepe et al, 2018;Martorelli et al, 2021). We relate the poor development of shallow-water contourites in the study area to the limited and distant sediment supply (e.g., Schattner et al, 2019) and due to the occurrence of wide shelves. Additionally, shallow-water contourites are usually fostered by interactions between currents and outstanding morpho-bathymetric features, such as faults or straits (Vandorpe et al, 2011;Pepe et al, 2018), which are absent in the study area.…”
Section: Significance Of Outer Shelf-upper Slope Contouritic Patternsmentioning
confidence: 99%
“…2b, 6, 7) may result from negligible flow velocities of water, as shown in the LLC2160 simulation. This quasi-stable zone lacks sediment deposition, facilitates mound buildups, and may also host percolation-related carbonate mounds, similar to its neighboring region of the Alpha Crucis ridge, which is located ~60 km southwest of the study area at around the same water depths (~400 to 700 mbsl; 44.55 • W, 24.95 • S; Maly et al, 2019).…”
Section: Effects Of Current Reversal and The Iwbcmentioning
confidence: 99%
“…In the southeast continental margin of Brazil, other geomorphological features also co-occur with carbonate mounds, such as saline diapirs and pockmarks. Recent studies have reported deep-sea carbonate mounds on the São Paulo Plateau and the Alpha Crucis Carbonate Ridge in the Santos Basin (Fujikura et al, 2017;Maly et al, 2019). These sites are significant for geological and biological reasons.…”
Section: Introductionmentioning
confidence: 99%